Corrosion inhibition of aluminium alloy by rhamnolipid biosurfactant derived from pseudomonas sp. PS-17. Issue 6 (2nd October 2018) - Zin, Ivan M.; Pokhmurskii, Vasyl I.; Korniy, Sergiy A.; Karpenko, Olena V.; Lyon, Stuart B.; Khlopyk, Olha P.; Tymus, Mariana B.
Abstract : Purpose: The purpose of this paper is to study the influence of rhamnolipid biosurfactant complex on the corrosion and the repassivation of a freshly cut Al-Cu-Mg aluminium alloy surface. Design/methodology/approach: The electrochemical methods, supported by quantum-chemical calculations and scanning electron microscopy data, were used. Findings: It was established that the rhamnolipid biosurfactant effectively inhibits corrosion of the alloy in synthetic acid rainwater. The efficiency of inhibition becomes stronger with the increase of biosurfactant concentration; however, above the critical micelle concentration, the further improvement in inhibition is minor. It is believed that the mechanism of corrosion inhibition is related to the adsorption of the biosurfactant molecule on the aluminium alloy surface and the formation of a barrier film; however, the formation of a complex compound (salt film) between aluminium ions and rhamnolipid on anodic sites of the alloy is not ruled out. In case of surface mechanical activation of the alloy, the biosurfactant molecule effectively prevents corrosion. Furthermore, addition of the biosurfactant to the corrosion environment increases the repassivation kinetics of the alloy by two to four times as compared with an uninhibited environment. Practical implications: The commercial impact of the study consists in the possibility of obtaining of environmentally safe corrosion inhibitors of aluminium alloys by biosynthesis from renewable agricultural raw materials. Originality/value: The originality of this paper is to study the effectiveness of "green" corrosion inhibitor based on biogenic product on freshly generated surface of aluminium alloy.